Social tensions - Administrative responses - Pereira, Maxwell (2002)
The article classifies various types and sources of social tension. It focuses on the role of enforcing agencies in containing conflicts and tensions. However, the most important factor, according to the author, is the police-citizen relationship. He shows how experiments have been made over the years in the policing system to make it more people-friendly. The citizens' cooperation and participation with police has helped in keeping the rate of petty crime under control. An unbiased political leadership and an enlightened society can make the task of maintaining law and order significantly efficient and effective. - Reproduced.
Keywords: Social conflicts; Police